A five-level multilevel topology utilizing multicarrier modulation technique - Rabiya Rasheed; Saju K K; Bindu V (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents a new topology for cascaded H-bridge multilevel inverter utilizing multicarrier modulation technique. The new five-level topology utilizes a capacitive divider network consisting of two capacitors for producing output voltage levels. The developed circuit has reduced number of switches and dc sources compared to conventional five level inverters. Five main power switches, a single additional diode apart from antiparallel diodes, two capacitors and a dc supply constitute a single five level unit. Simulations as well as experimental results are verified for the new topology utilising multicarrier modulation technique with reduced harmonic distortions in the output.